A comparison of cognitive function in former Rugby Union players compared with former non-contact-sport players and the impact of concussion history - Hume, P. A.; Theadom, A.; Lewis, G. N.; Quarrie, K. L.; Brown, S. R.; Hill, R.; Marshall, S. W. (Sports Medicine, 2017)
Aim: This study investigated differences in cognitive function between former rugby and non-contact-sport players, and assessed the association between concussion history and cognitive function. Methods: Overall, 366 former players (mean ± standard deviation [SD] age 43.3 ± 8.2 years) were recruited from October 2012 to April 2014. Engagement in sport, general health, sports injuries and concussion history, and demographic information were obtained from an online self-report questionnaire. Cognitive functioning was assessed using the online CNS Vital Signs neuropsychological test battery. Cohen`s d effect size statistics were calculated for comparisons across player groups, concussion groups (one or more self-reported concussions versus no concussions) and between those groups with CNS Vital Signs age-matched norms (US norms). Individual differences within groups were represented as SDs. Results: The elite-rugby group (n = 103) performed worse on tests of complex attention, processing speed, executive functioning, and cognitive flexibility than the non-contact-sport group (n = 65), and worse than the community-rugby group (n = 193) on complex attention. The community-rugby group performed worse than the non-contact group on executive functioning and cognitive flexibility. Compared with US norms, all three former player groups performed worse on verbal memory and reaction time; rugby groups performed worse on processing speed, cognitive flexibility and executive functioning; and the community-rugby group performed worse on composite memory. The community-rugby group and non-contact-sport group performed slightly better than US norms on complex attention, as did the elite-rugby group for motor speed. All three player groups had greater individual differences than US norms on composite memory, verbal memory and reaction time. The elite-rugby group had greater individual differences on processing speed and complex attention, and the community-rugby group had greater individual differences on psychomotor speed and motor speed. The average number of concussions recalled per player was greater for elite rugby and community rugby than non-contact sport. Former players who recalled one or more concussions (elite rugby, 85 %; community rugby, 77 %; non-contact sport, 23 %) had worse scores on cognitive flexibility, executive functioning, and complex attention than players who did not recall experiencing a concussion. Conclusions: Past participation in rugby or a history of concussion were associated with small to moderate neurocognitive deficits (as indicated by worse CNS Vital Signs scores) in athletes post retirement from competitive sport.